Gejala Komunikasi Interpersonal antara Desainer Grafis dan Klien dalam Proses Pembuatan Desain - Akhmad Abu Khasan Muzakki (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Interpersonal communication is a type of communication that is often encountered and used in daily activities. Likewise, this type of communication is used in the design creation process, especially in interactions between graphic designers and clients. In practice, graphic designers often face challenges in understanding client needs, processing ideas, and making creative decisions. Challenges that often arise in the design process include mismatching client expectations, inconsistent requests, misunderstandings in translating client needs into designs, as well as various other external challenges that can influence design results. Phenomenon in the field shows that designers often experience internal conflict when balancing creativity with client requests. Therefore, understanding the dynamics of intrapersonal communication in the design process is crucial in order to produce work that meets the client's expectations without sacrificing creativity and aesthetic value in a graphic design.